A spatial multicriteria decision-making method for natural gas transmission pipeline routing. Issue 5 (4th May 2017) - Yildirim, Volkan; Yomralioglu, Tahsin; Nisanci, Recep; Çolak, H. Ebru; Bediroğlu, Şevket; Saralioglu, Ekrem
Abstract: In accordance with current demands, the natural gas transmission pipeline (NGTP) is one of the most appropriate methods used in the distribution of existing reserves. Construction of long-distance pipelines requires large expenditures. Decreasing the time and cost of such construction and minimising environmental damage depend upon identifying the optimum routes from the onset of the project. Route determination is one of the most important steps in NGTP projects. The route determination process requires obtaining the existing graphic and non-graphic data from different institutions and organisations, as well as gathering, storing, querying and analysing non-existing data in an appropriate and efficient manner. Accessing the correct results rapidly by analysing such large data-sets can be achieved with spatial multicriteria decision-making technologies based on the geographic information system as an effective decision support tool. In this study, three methods were implemented for two NGTP projects of 103.60 and 60.89 km in length. At the end of this study, it was concluded that Spatial technique for order preference by similarity to ideal solution was the most effective of the three pipeline routing methods and that it could reduce project costs by approximately 21%.